Analisis Motivasi Berkunjung Wisatawan Wellness Berbasis Meditasi (Studi Kasus: Mayakosha Pesagi Bali) - Satya Darma, Anak Agung Ngurah Agung; Gunawan, Jevon; Kusumawidjaya, Erris (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2025)
This study aims to explore the motivations of wellness tourists visiting Mayakosha Pesagi Bali by applying the push and pull motivation theory within a qualitative descriptive framework. Data were collected through in-depth interviews with seven participants who had experienced four main wellness activities at the destination. Thematic analysis reveals that internal motivations (push factors) include the desire for physical and emotional recovery, stress release, health maintenance, and spiritual balance. Meanwhile, external attractions (pull factors) encompass the serene mountain environment, personalized and professional wellness services, as well as the integration of local Balinese culture and spirituality. The findings show that wellness tourism at Mayakosha Pesagi offers not only relaxation but also a transformative healing experience. This research contributes to the understanding of wellness tourist behavior and provides insight for the development of similar destinations that emphasize holistic, authentic, and culturally grounded wellness experiences. Keywords: wellness tourism, motivation, push and pull theory, Mayakosha Pesagi, qualitative study